MethodologicalFrameworkforModelling EuropeanPassenger And Freight Transport on Transport Infrastructure Scenarios With the ETIS: MYSTIC: Towards Origin - Destination Matrices for Europe - Langeland, Anders (Proceedings from the Annual Transport Conference at Aalborg University, 2000)
This paper will present and describe the results from workpackage 4 of the MYSTIC project. The work done in MYSTIC relates to the Strategic Section of the Transport Research Programme within the 4th Framework of the EU research programme. The MYSTIC study is within the field “Understanding mobility”, which deals with “Information systems”. The INFOSTAT project created the conceptual basis for ETIS – European Transport policy Information System. The MYSTIC project deals with modelling of both passenger and freight flows, but only the passenger part will be presented in this paper. MYSTIC is one of several projects on the path towards creating ETIS, which will be very important for the Common Transport Policy.